PRODUCTION OF TiO2 PARTICLES BY SOL-GEL ULTRASOUND ASSISTED FOR PHOTOCATALYTIC APPLICATIONS - Martínez Rojas, Vanessa C. (2015)
Synthesis of TiO2 particles was made by sol-gel technique assisted of ultrasonic radiationfrom an alcoholic solution of titanium isopropoxide. Then was subjected to a heat treatmentin air at 350 °C for 1 h. X-ray diffraction and transmission electron microscopy confirmedthat the size of the crystalline domains is between 10 and 37 nm. Infrared spectroscopy studyconfirms the presence of -OH groups on the surface of TiO2. Modification of the morphologyand surface area, due to the influence of exposure time to the ultrasonic radiation, is evidencedby studies of SEM and BET respectively. Properties of TiO2 obtained were studied bymonitoring the degradation of solutions of methyl orange in the presence of UV-A radiation.It was observed that larger the ultrasonic radiation exposure during the TiO2 synthesis largerthe constant velocity for the photocatalytic reaction for the methyl orange.